A coronene-based semiconducting two-dimensional metal-organic framework with ferromagnetic behavior - Dong, Renhao; Zhang, Zhitao; Tranca, Diana C.; Zhou, Shengqiang; Wang, Mingchao; Adler, Peter; Liao, Zhongquan; Liu, Feng; Sun, Yan; Shi, Wujun; Zhang, Zhe; Zschech, Ehrenfried; et al. (Nature Communications, 2018)
Metal-organic frameworks (MOFs) have so far been highlighted for their potential roles in catalysis, gas storage and separation. However, the realization of high electrical conductivity (>10-3 S cm-1) and magnetic ordering in MOFs will afford them new functions for spintronics, which remains relatively unexplored. Here, we demonstrate the synthesis of a two-dimensional MOF by solvothermal methods using perthiolated coronene as a ligand and planar iron-bis(dithiolene) as linkages enabling a full π-d conjugation. This 2D MOF exhibits a high electrical conductivity of 10 S cm-1 at 300 K, which decreases upon cooling, suggesting a typical semiconductor nature. Magnetization and 57Fe Mössbauer experiments reveal the evolution of ferromagnetism within nanoscale magnetic clusters below 20 K, thus evidencing exchange interactions between the intermediate spin S = 3/2 iron(III) centers via the delocalized π electrons. Our results illustrate that conjugated 2D MOFs have potential as ferromagnetic semiconductors for application in spintronics.
CRIS-Team Scopus Importer:2022-04-14